2005
DOI: 10.1634/theoncologist.10-6-427
|View full text |Cite
|
Sign up to set email alerts
|

Risk Models for Predicting Chemotherapy-Induced Neutropenia

Abstract: Neutropenia and its complications, including febrile neutropenia, are major dose-limiting toxicities of systemic cancer chemotherapy. A number of studies have attempted to identify risk factors for neutropenia and its consequences to develop predictive models capable of identifying patients at greater risk for such complications and to guide more effective and costeffective applications of the colony-stimulating factors. A systematic review of the literature showed that age, performance status, nutritional sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
213
0
11

Year Published

2006
2006
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 290 publications
(236 citation statements)
references
References 53 publications
6
213
0
11
Order By: Relevance
“…[4][5][6] Major risk factors for the development of FN include older age, comorbid conditions, the type of cancer, and the type and number of myelosuppressive chemotherapy agents used. [5][6][7] FN represents a lifethreatening complication that requires urgent evaluation for the identification and treatment of documented or presumed infection. 8 Infection in the neutropenic cancer patient often can be difficult to identify because of the lack of neutrophils and associated clinical symptoms and signs.…”
Section: Fn and Early Mortalitymentioning
confidence: 99%
“…[4][5][6] Major risk factors for the development of FN include older age, comorbid conditions, the type of cancer, and the type and number of myelosuppressive chemotherapy agents used. [5][6][7] FN represents a lifethreatening complication that requires urgent evaluation for the identification and treatment of documented or presumed infection. 8 Infection in the neutropenic cancer patient often can be difficult to identify because of the lack of neutrophils and associated clinical symptoms and signs.…”
Section: Fn and Early Mortalitymentioning
confidence: 99%
“…Simulations showed that the impact of the different schedules was negligible. Several authors have suggested that female gender is among others a significant predictor of neutropenia and is considered a risk factor in the Guidelines for the use of Colony-Stimulating factors in Managing Neutropenia [27]. However, gender was not found as a clinically relevant covariate in PK/PD models for neutropenia although a statistical significance was shown [19,28].…”
Section: Absolute Neutrophil Count-time Profile Vpcmentioning
confidence: 99%
“…The risk of developing FN is normally associated with the cancer treatment. For example, hematological malignancies are associated with a higher risk of FN compared with solid tumors, due to the process of the disease and its treatment (21,22). When comparing solid tumors, patients with lung cancer appear to exhibit a higher incidence rate of FN (5).…”
Section: Discussionmentioning
confidence: 99%